Cognitive bias modification for adult’s depression: A systematic review and meta-analysis - Li, Jiawei; Ma, Hui; Yang, Hao; Yu, Haoran; Zhang, Ning (Frontiers in Psychology, 2023)
Abstract Objects This study aimed to elucidate the effect of cognitive bias modification on depression. Methods This research included 10 randomized studies searching four major databases: PubMed, EMBASE, PsycINFO and Cochrane Library, with a total sample size of 467. Moreover, they were examined for quality and possible publication bias. Results CBM had a statistical significance results g = -0.64, 95% CI = [-0.97 -0.32]. the interpretation of cognitive bias modification shows highest effect size g = -1.45, 95% CI = [-2.05 -0.88]. When the training place is located in the laboratory, the training effect is significant g = -1.11, 95% CI = [-1.62 -0.61]. the difference is statistically significant when the training environment was changed to home g = -0.28, 95% CI = [-0.51 -0.05]. CBM has a statistical effect on moderate to severe depression g = -0.70, 95% CI = [-1.04 -0.36]. Conclusion We found that CBM had a moderate therapeutic effect on depression, wherever the setting was at home or in the lab. Especially when the interpretation of cognitive bias modification (CBM-I) has been used, we got the highest effect value. Furthermore, CBM has a statistical effect on moderate to severe depression. Keywords cognitive bias modification, depression, review, meta-analysis